PRAKTIK PENGELOLAAN ZAKAT FITRAH PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM: Studi Kasus Di Masjid Jamie Al-Amin Kelurahan Ciakar Kecamatan Panongan Kabupaten Tangerang - Oktavia Nur Istiqomah; Irvan Iswandi (Melati Institute, 2022)
This study discusses The Practice of Managing Zakat Fitrah from The Perspective of Positive Law and Islamic Law ( Case Study in The Mosque Jamie AL-Amin village Office Ciakar Sub-district Panongan District Tangerang). With the focus of his research how to manage zakat fitrah in the Mosque Jamie Al-Amin, an assessment of how to manage zakat fitrah in the Mosque Jamie Al-Amin from the viewpoint of positive law and Islamic law. This study uses a qualitative method. Data sources used in the form of primary data and secondary data, by way of observation, interviews, documentation, and some literature relating to the management of zakat. While the analysis techniques used in this study include data reduction, data display, conclusion drawing and verification. From the results of research conducted by the author shows that: First, how to manage zakat fitrah in the Mosque Jamie Al-Amin in the management of zakat is in accordance with what they are deliberating and is in accordance with the management function of planning, organizing, implementation, supervision and evaluation. Second, assessment in managing zakat fitrah in the Mosque Jamie Al-Amin perspective positive law based on UU No.23 Tahun 2011 Pasal 2 regarding the management of legal certainty based zakat, committee or amil zakat in the Mosque Jamie Al-Amin not registered as Unit Pengumpul Zakat (UPZ) which is sheltered by state agencies Kantor Urusan Agama (KUA) sub-district which is part of Badan Amil Zakat Nasional (BAZNAS) or Lembaga Amil Zakat (LAZ). Third, assessment from the perspective of Islamic law in managing zakat fitrah in the Mosque Jamie Al-Amin shows that they have fulfilled the pillars and conditions of obligatory zakat but in the distribution of zakat fitrah prefers people who are known rather than poor and poor who really needs it.